A human-in-the-loop approach for enhancing mobile robot navigation in presence of obstacles not detected by the sensory set - Ferracuti, Francesco; Freddi, Alessandro; Iarlori, Sabrina; Monteriù, Andrea; Omer, Karameldeen Ibrahim Mohamed; Porcaro, Camillo (Frontiers in Robotics and AI, 2022)
Human-in-the-loop approaches can greatly enhance human-robot interaction by making the user an active part of the control loop, which can provide a feedback to the robot in order to augment its capabilities. Such feedback becomes even more important in all those situations where safety is of utmost concern, such as in assistive robotics. This study aims to realize a human-in-the-loop approach, where the human can provide a feedback to a specific robot, namely a smart wheelchair, to augment its artificial sensory set, extend and improve its capabilities to detect and avoid obstacles. The feedback is provided by both a keyboard and a brain-computer interface: with this scope, the work has also included a protocol design phase to elicit and evoke human brain event-related potentials. The whole architecture has been validated within a simulated robotic environment, with electroencephalography signals acquired from different test subjects.